Adoption and Impact of Cloud Computing in Small and Medium Enterprises A Systematic Review - Oriza, Rahmat; Maulidar (Journal Informatic, Education and Management (JIEM), 2024)
This research aims to investigate the adoption and impact of cloud computing on Small and Medium Enterprises (SMEs) through a systematic approach. The research method involves analyzing a number of relevant and verified scientific articles, focusing on technology adoption, benefits gained, and challenges faced by SMEs in adopting cloud computing technology. The analysis results show that cloud computing adoption among SMEs has significantly increased in recent years, with benefits including operational efficiency, scalability, and data accessibility. However, there are some obstacles faced, including data security issues, resource limitations, and challenges in integrating with existing systems. In conclusion, although cloud computing adoption holds great potential benefits for SMEs, associated challenges need to be addressed with careful strategies.